The Influence of Profitability, Leverage, and Liquidity on Company Value in The Property Sector (Tbk) Listed on The Indonesian Stock Exchange (IDX) In 2024 - Wijaya, Moch. Hamied; Ariyanto, Eny (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study analyzes the effect of profitability (return on assets/ROA, return on equity/ROE), leverage (DER), and liquidity (CR) on company value (PBV) in 41 property companies listed on the Indonesia Stock Exchange (IDX) in 2024. Using multiple linear regression analysis to test the hypothesis, and with all classical assumptions fulfilled (normality, multicollinearity, heteroscedasticity, autocorrelation, linearity) to ensure the validity of the regression model, a coefficient of determination of R² = 51.2% was obtained. These results suggest that profitability is a significant factor in valuation, as indicated by signal theory, where asset efficiency and return on equity serve as credible signals of management's ability to generate sustainable cash flows from long property development cycles. ROA and ROE have a significant positive effect, while CR and DER are insignificant. These findings are consistent with agency theory and trade-off theory in the context of the emerging market recovery phase. Large-cap companies (assets > IDR 20 trillion) excel through economies of scale in land banks and vertical integration, creating a significant valuation premium compared to mid-cap companies. Management implications emphasize targeting ROA/ROE >25% through aggressive pre-sales and financial engineering, while investors are advised to screen for undervalued issuers systematically. This study fills the empirical gap post-Omnibus Law, becoming a benchmark for the transformation of Indonesian property valuation towards optimal PBV.